Long‐term antagonism and allosteric regulation of mu opioid receptors by the novel ligand, methocinnamox - Joshua C. Zamora; Hudson R. Smith; Elaine M. Jennings; Teresa S. Chavera; Varun Kotipalli; Aleasha Jay; Stephen M. Husbands; Alex Disney; Kelly A. Berg; William P. Clarke (Wiley, 2021)
Abstract Opioid overdose is a leading cause of death in the United States. The only treatment available currently is the competitive antagonist, naloxone (Narcan®). Although naloxone is very effective and has saved many lives, as a competitive antagonist it has limitations. Due to the short half‐life of naloxone, renarcotization can occur if the ingested opioid agonist remains in the body longer. Moreover, because antagonism by naloxone is surmountable, renarcotization can also occur in the presence of naloxone if a relatively larger dose of opioid agonist is taken. In such circumstances, a long‐lasting, non‐surmountable antagonist would offer an improvement in overdose treatment. Methocinnamox (MCAM) has been reported to have a long duration of antagonist action at mu opioid receptors in vivo. In HEK cells expressing the human mu opioid receptor, MCAM antagonism of mu agonist‐inhibition of cAMP production was time‐dependent, non‐surmountable and non‐reversible, consistent with (pseudo)‐irreversible binding. In vivo, MCAM injected locally into the rat hindpaw antagonized mu agonist‐mediated inhibition of thermal allodynia for up to 96 h. By contrast, antagonism by MCAM of delta or kappa agonists in HEK cells and in vivo was consistent with simple competitive antagonism. Surprisingly, MCAM also shifted the concentration‐response curves of mu agonists in HEK cells in the absence of receptor reserve in a ligand‐dependent manner. The shift in the [D‐Ala2,N‐MePhe4,Gly‐ol5]‐enkephalin (DAMGO) concentration‐response curve by MCAM was insensitive to naloxone, suggesting that in addition to (pseudo)‐irreversible orthosteric antagonism, MCAM acts allosterically to alter the affinity and/or intrinsic efficacy of mu agonists.